Pacing and predictors of performance during cross-country skiing races: A systematic review - Stöggl, T.; Pellegrini, B.; Holmberg, H. C. (Journal of Sport and Health Science, 2018)
Background: Cross-country skiing (XCS) racing, a popular international winter sport, is complex and challenging from physical, technical, and tactical perspectives. Despite the vast amount of research focusing on this sport, no review has yet addressed the pacing strategies of elite XCS racers or the factors that influence their performance. The aim was to review the scientific literature in an attempt to determine the effects of pacing strategy on the performance of elite XCS racers. Methods: Four electronic databases were searched using relevant subject headings and keywords. Only original research articles published in peerreviewed journals and the English language and addressing performance, biomechanics, physiology, and anthropometry of XCS racers were reviewed.